Simulation of the stress regime during grain filling in bamboo reinforced concrete silo. (September 2019) - Jayachandran, Lakshmi E.; Nitin, B.; Rao, Pavuluri Srinivasa
Abstract: Design and development of low-cost farm silos call for a strong understanding of its structural performance and loads. Limited studies address the effect of stored grains on silos. A farm level bamboo reinforced concrete (BRC) silo with a flat bottom has been designed for the storage of rough rice. A full-scale 3D finite element (FE) model of the BRC silo has been developed and the grain filling in progressive layers simulated in the ANSYS ® software. The stored grain and silo body interactions have been modeled considering the characteristic properties of both rough rice as well as the BRC, with minimal simplifications. The numerical results have been compared with the outcomes of classical theories (Jannsen's and Reimbert's) and design code (IS 4995-1974). While a significant difference was observed between the lateral stress magnitudes predicted by the numerical and analytical methods, the axial wall stresses from FEM approach deviated from the IS code values by 16%. Contrary to the analytical approaches, FEM predicted non-uniform stress distribution due to the bulk grain at the silo bottom. The numerical approach could also identify the localized peak pressures and stress distribution patterns within the grain layers, which is usually beyond the scope of analytical techniques. Possible reasons for fluctuations in stress patterns are discussed in detail. The study unveiled the intricacies involved in the FEM and the analytical outcomes while predicting the stresses in small and medium scale silos intended for use on farms. Highlights: Stresses in bamboo reinforced concrete silo was estimated by finite element method. Numerical results were compared with classic theories and IS 4995-1974. Finite element method captured possible local peak pressures at silo bottom. Non-uniformity of stresses at silo bottom observed using the FEM. Sensitivity of the numerical results to changes in material properties investigated.